Comparison of the efficiency of antiaggregative therapy in patients with first arisen and progressive angina pectoris to influence the fatty acid spectrum of platelet membrane phospholipids - Zavalska, T.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
The study involved 71 patients: 25 patients with first arisen angina pectoris (FAAP) and 46 patients with progressive angina pectoris (PAP) (II group). Patients received basic antianginal treatment, which included antiplatelet therapy. Most of the patients took aspihrel (FAAP 14 and 29 of the PAP), and a smaller proportion of patients in the presence of contraindications took clopidogrel (FAAP 11 and 17 of the PAP). The fatty acid spectrum of phospholipids in the platelet membranes was studied. The examination of patients was conducted in the first 2–3 days of hospital stay and after 21–22 days after treatment. The results showed that the treatment of FAAP and PAP patients using aspigrel as compared with clopidogrel found a positive trend of the platelet membrane performance.